Linking the occurrence of cutaneous opportunistic fungal invaders with elemental concentrations in false killer whale (Pseudorca crassidens) skin. Issue 5 (1st July 2015) - Mouton, Marnel; Przybylowicz, Wojciech; Mesjasz‐Przybylowicz, Jolanta; Postma, Ferdinand; Thornton, Meredith; Archer, Edward; Botha, Alfred
Summary Cetaceans, occupying the top levels in marine food chains, are vulnerable to elevated levels of potentially toxic trace elements, such as aluminium (Al), mercury (Hg) and nickel (Ni). Negative effects associated with these toxic metals include infection by opportunistic microbial invaders. To corroborate the link between the presence of cutaneous fungal invaders and trace element levels, skin samples from 40 stranded false killer whales (FKWs) were analysed using culture techniques and inductively coupled plasma‐mass spectroscopy. Twenty‐two skin samples yielded 18 clinically relevant fungal species. While evidence for bioaccumulation of Hg in the skin of the FKWs was observed, a strong link was found to exist between the occurrence of opportunistic fungal invaders and higher Al : Se and Al : Zn ratios. This study provides indications that elevated levels of some toxic metals, such as Al, contribute to immunotoxicity rendering FKWs susceptible to colonization by cutaneous opportunistic fungal invaders.